Sutcliffiella deserti sp. nov., isolated from desert soil. Issue 2 (23rd February 2022) - Bai, Pengze; Zhang, Siyue; Chen, Ya; Ping, Weiwei; Pang, Huancheng; Du, Jie; Li, Yuyi; Zhang, Jianli
Abstract : A Gram-stain-positive, facultative anaerobic, motile and rod-shaped bacterial strain, DG-18 T, was isolated from desert soil sampled at the Kubuqi Desert in Inner Mongolia, China. Strain DG-18 T grew at 4–40 °C (optimum, 25–30 °C), at pH 8.0–10.0 (optimum, pH 9.0) and with 0–8.0 % (w/v) NaCl (optimum 2.0%). 16S rRNA gene sequence analysis placed strain DG-18 T within the genus Sutcliffiella of the family Bacillaceae with Sutcliffiella halmapala DSM 8723 T (98.2%), Sutcliffiella zhanjiangensis JSM 099021 T (97.6%), Sutcliffiella horikoshii DSM 8719 T (97.4%), Sutcliffiella catenulata 18C T (96.6 %) and Sutcliffiella cohnii NBRC 15565 T (96.5%) as its closest relatives. The major respiratory quinone of strain DG-18 T was MK-7 and the major polar lipids consisted of diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol. Its major fatty acids were iso-C15 : 0 and iso-C17 : 1  ω 10 c . The genomic DNA G+C content of strain DG-18 T was 38.7 mol% based on total genome calculations. The average nucleotide identity score between the genomic sequence of strain DG-18 T and that of S. halmapala DSM 8723 T was 76.7 %. The Genome-to-Genome Distance Calculator showed that the DNA–DNA hybridization value for strain DG-18 T and S. halmapala DSM 8723 T was 21.8%. Based on the polyphasic taxonomic data, strain DG-18 T represents a novel species of the genus Sutcliffiella, for which the name Sutcliffiella deserti sp. nov. is proposed. The type strain is DG-18 T (=GDMCC 1.17773 T =KCTC 43170 T ).